Asymmetric Bilateral Lichen Striatus: A Rare Presentation following Multiple Blaschko’s Lines - Jeffrey S. Dickman; McKay D. Frandsen; Andrew J. Racette (Case Reports in Dermatological Medicine)
Lichen striatus (LS) is an uncommon, acquired, self-limited, and benign linear dermatosis of unknown etiology that most often occurs unilaterally and is confined to the lines of Blaschko. A healthy 7-year-old girl presented to our clinic with bilateral asymmetric LS occurring on the right arm and left leg of 1-year duration. Very few cases of bilateral LS have been previously reported in the literature, with none from clinics within the United States. The etiology of LS is currently unknown; however its confinement to Blaschko’s lines, which represent embryologic migration of skin cell clones, does provide insight into a possible pathogenesis. It seems most likely that an individual’s development of LS is linked to their genetic predisposition and a subsequent triggering event. Our case serves as a strong example of a rare presentation of LS and facilitates discussion of the clinical diagnostic process and possible pathogenesis of this dermatosis.